A new cave-dwelling species of Bisetocreagris Ćurčić (Arachnida, Pseudoscorpiones: Neobisiidae) from Yunnan Province, China - Li, Yun-Chun; Shi, Ai-Min; Liu, Huai (Entomologica Fennica, 2017)
A new pseudoscorpion species, Bisetocreagris xiaoensis Li & Liu, sp. n., is described and illustrated from specimens collected in caves in Yanjin County, Yunnan Province, China. An identification key is provided to all known cavedwelling representatives of the genus Bisetocreagris in the world.